2013
DOI: 10.3747/co.20.1323
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Patient Knowledge of Clinical Trials and Trialist Priorities

Abstract: by clinical trialists. The findings suggest that when developing education interventions, emphasis should be placed on the topics most directly related to patient care, and factors such as age and education level should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 24 publications
(40 reference statements)
6
34
2
Order By: Relevance
“…Studies have found that English speakers have a low comprehension of clinical trial terminology and procedures. 12,24 Areas of potential confusion among clinical trial participants regardless of language include the nature and purpose of randomization 10,11,12,24 and the ability of participants to voluntarily withdraw from a study. 24 Even when patient protections are explained, some patients may worry that their safety is still at risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that English speakers have a low comprehension of clinical trial terminology and procedures. 12,24 Areas of potential confusion among clinical trial participants regardless of language include the nature and purpose of randomization 10,11,12,24 and the ability of participants to voluntarily withdraw from a study. 24 Even when patient protections are explained, some patients may worry that their safety is still at risk.…”
Section: Discussionmentioning
confidence: 99%
“…12,24 Areas of potential confusion among clinical trial participants regardless of language include the nature and purpose of randomization 10,11,12,24 and the ability of participants to voluntarily withdraw from a study. 24 Even when patient protections are explained, some patients may worry that their safety is still at risk. 10 It may be particularly challenging to address such concerns through the informed consent and study enrollment process when a patient does not speak English.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was based on statements from HCPs and like several other studies reinforce the education of healthcare professionals on Clinical Research to boost recruitment rates (11). Another survey based study on the knowledge of CT (16) demonstrated that knowledge of participants on CT was limited especially on topics such as rationale of study, randomization and placebo and patient protection. Participants were less informed about the agencies conducting CT in Mauritius leading to the belief that CT was performed on a selection of people.…”
Section: Discussionmentioning
confidence: 85%
“…While raising trial participation awareness is an important first step, the patient community also needs access to information about what it means to participate in research, including explanations on the trial process, different types of trials, the informed consent process and regulatory and patient protections that govern research [6]. This education must also include demystifying key myths that are long held beliefs, often deeply ingrained in the lay community.…”
Section: Dissecting the Problem: Why Is There Poor Participation In Cmentioning
confidence: 98%
“…Over 90% of enrolled PPMI subjects are Caucasian. Numerous papers have focused on the challenge of enrolling minorities in clinical research, so we will not delve into the potential reasons behind poor research participation rates, but it is a problem faced in PD as well as in other diseases [6]. Our experience with PPMI recruitment and minority enrollment is that broad tactics cannot be assumed to work for all groups and that a strong emphasis on how recruitment approaches ought to be tailored to be able to effectively communicate and conduct outreach to different communities should be part of every recruitment plan.…”
Section: ■ Case Study: the Parkinson's Progression Markers Initiativementioning
confidence: 99%